A METHOD FOR ISOLATING INTACT MITOCHONDRIA AND NUCLEI FROM THE SAME HOMOGENATE, AND THE INFLUENCE OF MITOCHONDRIAL DESTRUCTION ON THE PROPERTIES OF CELL NUCLEI - Dounce, Alexander L. (The Rockefeller University Press, 1955)
1. An improved type of ground glass homogenizer for soft tissues has been described which brings about a high degree of cell disruption and liberation of nuclei without causing appreciable damage to mitochondria. The gentleness and effectiveness of the new homogenizer in respect to isolation of mitochondria have been ascertained by comparing the ATP-ase activities of mitochondria isolated in 0.25 M sucrose solution without pH adjustment using a previous type of homogenizer with those of mitochondria isolated under the same conditions with the aid of the new homogenizer. In these experiments sucrose of 0.25 molarity without pH adjustment has been used in order to maintain the mitochondria in a rather sensitive state so as to make slightly deleterious effects of homogenization readily apparent. 2. A new method is described for the isolation of morphologically intact mitochondria and cell nuclei from the same homogenate. In this procedure the pH of the homogenate in 0.44 M sucrose is maintained at 6.0–6.2 with citric acid during the homogenization. An alternative method employing 0.44 M sucrose plus 0.005 M CaCl(2) is given for the isolation of nuclei from tumor cells. However, the latter method does not produce unaltered mitochondria. 3. The α-ketoglutarate, malate, succinate, and hexanoate oxidases of the "intact" mitochondria isolated in 0.44 M sucrose adjusted to pH 6.0–6.2 with very dilute citric acid as described in this paper have been investigated, and it has been shown that the mitochondria compare favorably to those isolated in 0.25 M sucrose by a previously described method. 4. Mitochondria have been found to contain an enzyme which causes nuclei to lose their ability to form gels in dilute alkali. This enzyme is released from the mitochondria when the latter are disrupted. 5. Some properties of nuclei isolated by the new method have been briefly discussed.